Quality assessment of vitamin D metabolite assays used by clinical and research laboratories. Issue 173 (October 2017) - Carter, G.D.; Berry, J.; Durazo-Arvizu, R.; Gunter, E.; Jones, G.; Jones, J.; Makin, H.L.J; Pattni, P.; Phinney, K.W.; Sempos, C.T.; Williams, E.L.
Highlights: DEQAS (the Vitamin D External Quality Assessment Scheme) monitors the analytical performance of total 25-OHD, 1, 25(OH)2 D and 24, 25(OH)2 D. Some immunoassays under-recover 25-OHD2 . In some methods, modest increases in endogenous triglyceride causes a spurious decrease in total 25-OHD results. There is considerable method – related variability among results for 1, 25(OH)2 D. Results for 24, 25(OH)2 D are variable, possibly due to differences in standardization. Abstract: The Vitamin D External Quality Assessment Scheme (DEQAS) was launched in 1989 and monitors the performance of 25-hydroxyvitamin D (25-OHD) and 1, 25- dihydroxyvitamin D (1, 25(OH)2 D) assays. In April 2015 a pilot scheme for 24, 25-dihydroxyvitamin D (24, 25(OH)2 D) was introduced. The 25-OHD scheme is accuracy − based with target values assigned by the NIST Reference Measurement Procedure (RMP) for 25-OHD2 and 25-OHD3 . A similar method is used to assign values for 3-epi-25-OHD. Five samples of human serum are distributed quarterly to over 1000 participants in 58 countries (April 2016) and clinical laboratories are expected to submit results within approximately 5 weeks. Research laboratories with assays run less frequently are not given a deadline. Archived samples with NIST- assigned values are also available. Performance is assessed on the first four samples with the fifth reserved for investigations e.g. recovery experiments or to assess the influence of other serum constituents such as lipids. DEQAS provides rapid feedback, with an on-line preliminary report available immediately after a participant submits results and a comprehensive report soon after the results deadline. In 2015, DEQAS investigations revealed that several 25-OHD immunoassays under-recovered 25-OHD2 and 25-OHD results were falsely low on a sample with a modestly raised triglyceride concentration. An RMP for 1, 25 (OH)2 D is not yet available and results are judged against the Method Mean. Free advice is available from the DEQAS Advisory Panel which includes experts on methodology and biostatistics. DEQAS collaborates closely with the Vitamin D Standardization Program (VDSP) and both organizations have successfully worked with participants and manufacturers to improve the accuracy of vitamin D assays.